This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: = a in the translation theorem. Therefore t e t t f 2 ) ( − = Problem 9 Apply the translation theorem to find the inverse Laplace transforms of the functions. 25 6 5 3 ) ( 2 + − + = s s s s F ) ( s F can be rewritten as 16 ) 3 ( 14 16 ) 3 ( ) 3 ( 3 16 ) 3 ( 9 5 ) 3 ( 3 ) ( 2 2 2 + − + + − − = + − + + − = s s s s s s F t t t f sin cos ) ( . This transform corresponds to an inverse of the form + = . However we have instead of s . So in the translation theorem. 3 − s 3 = a Therefore ) 4 sin ) 2 / 7 ( 4 cos 3 ( ) ( 3 t t e t f t + =...
View
Full Document
 Spring '11
 HAFTKA
 Laplace, translation theorem

Click to edit the document details